The Mynshall lute book - Mynshall, Richard; Spencer, Robert 1932-1997 (Leeds Boethius Press, 1975)
Contains anonymous works and works by J. Dowland, J. Johnson, J. Taverner, and Lusher.Tablature notation.Photoreproduction of a 16th-17-cent. ms. originally owned and in part written by R. Mynshall, of Nantwich, Cheshire